Health monitoring of metallic structures using electromechanical impedance technique - Qi, Weichen (2014)
The electromechanical impedance (EMI) method, which applies piezoelectric ceramic lead-zirconate-titarate (PZT) as impedance transducers, is proven to be an effective technique for structure health monitoring. This study examines the efficacy of using PZT transducers to detect any damage in specific part of structure. The study consists of two parts, experiment study and numerical modal analysis. Steel plate specimens with surface bonded PZT sensors were used in the experiment. Different damage in form of increasing size of holes were incurred on the specimen. The impedance results obtained were then compared and analyzed by observing the changes of conductance peaks and further illustrated by a statistical method, known as root mean square deviation (RMSD). The second part is modal analysis using ANSYS software. Models were built to predict the resonant frequencies under different damage condition. The data was subsequently compared to experimental results to check the accuracy of experiments.